Location, age, and race matter: a path model of emotional distress in the U.S. during COVID-19 - Viktor Clark; Hannah Ming; Sunny Jung Kim (BMC Public Health, 2023)
Abstract Background We aim to identify factors that explain emotional distress among underserved populations during the COVID-19 pandemic. Methods Starting in August 2020, we conducted an online epidemiological survey among 947 U.S. adults. The survey asked a wide array of constructs, including demographics, past-month substance use, and psychological distress. We developed a path model to understand how financial strain, age, and substance use are associated with emotional distress among People of Color (POC) and those living in rural areas. Results 22.6% (n = 214) of participants were POC; 114 (12%) resided in rural areas; 17.2% (n = 163) made between $50,000 and $74,999 annually; and the emotional distress average was 1.41 (SD = 0.78). POC, especially those younger, experienced higher rates of emotional distress (p < .05). People living in rural contexts reported lower rates of emotional distress through low alcohol intoxication and less financial strain (p < .05). Conclusions We found mediating factors related to emotional distress among vulnerable populations during the COVID-19 pandemic. Younger POC experienced higher rates of emotional distress. People in rural communities had less emotional distress when they had fewer days spent intoxicated by alcohol, which was associated with lower financial strain. We conclude with a discussion of important unmet needs and future research directions.